2017
DOI: 10.1155/2017/6825493
|View full text |Cite
|
Sign up to set email alerts
|

HIV as a Cause of Immune Activation and Immunosenescence

Abstract: Systemic immune activation has emerged as an essential component of the immunopathogenesis of HIV. It not only leads to faster disease progression, but also to accelerated decline of overall immune competence. HIV-associated immune activation is characterized by an increase in proinflammatory mediators, dysfunctional T regulatory cells, and a pattern of T-cell-senescent phenotypes similar to those seen in the elderly. These changes predispose HIV-infected persons to comorbid conditions that have been linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 214 publications
(227 reference statements)
6
94
0
4
Order By: Relevance
“…During HIV infection there is a general activation of the immune system . We investigated the activation profile of γδ T cells in EPI and LPI groups by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…During HIV infection there is a general activation of the immune system . We investigated the activation profile of γδ T cells in EPI and LPI groups by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent microbial translocation from the gastrointestinal tract to the systemic circulation is only partially reduced in patients receiving effective therapy [112-114]. The HIV-associated strong increase in IFN-α, IFN-γ, TNF-α, and IL-6 [115] also causes a profound depletion of CD4+ cells from the gut that is incompletely reversed by ART [114]. On the other hand, Keating et al [63, 110], aiming at describing the qualitative and quantitative nature of cytokine perturbation, reported that treatment-naive HIV patients have decreased serum levels of IL-15 and IL-12 as well as IFN-γ inducible protein-10 (IP-10) and TNF-α, while HAART-treated patients showed cytokine profiles more similar to those observed in uninfected individuals.…”
Section: Art and Inflammationmentioning
confidence: 99%
“…It has been reported that certain age-related NICMs like diabetes mellitus, cardiovascular disease, cancer, bone fracture and renal failure, are more common among HIV-1 infected individuals as compared to the general population. Exposure to prolonged cART along with low grade inflammation and persistent immune activation seen in HIV-infection is thought to be the cause for the increased risk of NICMs [2,10]. Chronic inflammatory conditions and persistent immune activation are believed to be the major drivers of aging physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Though treatment successfully controls HIV-replication and prevents opportunistic infections, HIV-infected persons on long term ART not only succumb to death at an earlier age than the HIVuninfected counterparts but also suffer from some maladies that are typically associated with human aging (Deeks, 2011). The effect of HIV-associated inflammation and immune activation on premature onset of immunosenescence despite effective viral suppression are thought to be the primary reasons for early aging in people living with HIV (PLHIV) (Sokoya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%